Effects of bacteria-enzyme co-fermented Chinese herbal medicine on growth performance, apparent nutrient digestibility, meat quality, and immune function in broilers - Ding, Peng; Wang, Xiong; Jiang, Sai; Li, Minxi; He, Xi; Peng, Yanmei (Frontiers in Veterinary Science, 2025)
This experiment aimed to investigate the effects of bacteria-enzyme co-fermented Chinese herbal medicine on growth performance, apparent nutrient digestibility, meat quality, and immune function in broilers. Four hundred one-day-old, uniformly healthy Arbor Acres broiler chicks were randomly divided into 5 groups with 8 replicates of 10 chicks each. Using a single-factor randomized design, the control group received a basal diet, the unfermented herbs group received the basal diet supplemented with 1% unfermented Chinese herbal medicine, and three treatment groups received the basal diet supplemented with 0.5, 1, and 1.5% bacteria-enzyme co-fermented Chinese herbal medicine, respectively. The feeding trial lasted 42 days. Upon completion, three broilers were randomly selected from each replicate for a 4-day metabolism trial to determine apparent nutrient digestibility. Results showed that compared to the control group, the final body weight and average daily gain were significantly increased (p < 0.05), and the feed-to-gain ratio was significantly decreased (p < 0.05) in the groups supplemented with 1 and 1.5% co-fermented herbs. The apparent digestibility of dry matter, crude ash, and gross energy was significantly higher (p < 0.05) in the 1 and 1.5% co-fermented herbs groups than in the control group. All three co-fermented herbs supplementation groups exhibited significantly higher apparent digestibility of crude protein, ether extract, and crude fiber compared to the control group (p < 0.05). Breast muscle drip loss and shear force were significantly reduced (p < 0.05) in the 1 and 1.5% co-fermented herbs groups compared to the control, with no significant difference between these two groups (p > 0.05). All herbs-supplemented groups showed significantly higher serum IgA, IgG, and IL-2 levels and significantly lower IL-1β levels than the control group (p < 0.05). In conclusion, supplementing Arbor Acres broiler diets with bacteria-enzyme co-fermented Chinese herbal medicine effectively enhanced growth performance and apparent nutrient digestibility, improved meat quality, and boosted immune function. Comprehensive consideration suggests that the recommended inclusion level of bacteria-enzyme co-fermented Chinese herbal medicine in Arbor Acres broiler diets under this experimental condition is 1%.